2013
DOI: 10.1371/journal.pone.0081044
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Relationships between Intimate Partner Violence and HIV/AIDS

Abstract: BackgroundIntimate partner violence (IPV) is a significant health problem that has been associated with HIV infection in numerous studies. We aimed to systematically review the literature on relationships between IPV and HIV in order to describe the prevalence of IPV in people with HIV, the prevalence of HIV in people experiencing IPV, the association between IPV and HIV, and evidence regarding mechanisms of risk and interventions.MethodsData sources were 10 electronic databases and reference lists. Studies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 94 publications
(291 reference statements)
5
98
1
1
Order By: Relevance
“…A growing body of evidence shows that the HIV epidemic and the IPV burden overlap geographically. A systematic review showed that 10 studies from different regions of the world (East Africa, India, Papua New Guinea, the US, and Mexico) reported high prevalence rates of HIV in women exposed to IPV, and that HIV-infected women were more likely to have experienced multiple forms of IPV than HIVuninfected women (Kouyoumdjian et al, 2013).…”
Section: What Is the Geographical Overlap Between Ipv And Hiv?mentioning
confidence: 99%
See 4 more Smart Citations
“…A growing body of evidence shows that the HIV epidemic and the IPV burden overlap geographically. A systematic review showed that 10 studies from different regions of the world (East Africa, India, Papua New Guinea, the US, and Mexico) reported high prevalence rates of HIV in women exposed to IPV, and that HIV-infected women were more likely to have experienced multiple forms of IPV than HIVuninfected women (Kouyoumdjian et al, 2013).…”
Section: What Is the Geographical Overlap Between Ipv And Hiv?mentioning
confidence: 99%
“…A second recent systematic review examined the relationship between IPV and HIV, exploring the mechanisms behind this relationship (Kouyoumdjian et al, 2013). A synthesis of these findings is presented below.…”
Section: What Are the Mechanisms Driving This Association?mentioning
confidence: 99%
See 3 more Smart Citations